2014
DOI: 10.1016/j.envres.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal air pollution exposure and ultrasound measures of fetal growth in Los Angeles, California

Abstract: Background Few previous studies examined the impact of prenatal air pollution exposures on fetal development based on ultrasound measures during pregnancy. Methods In a prospective birth cohort of more than 500 women followed during 1993-1996 in Los Angeles, California, we examined how air pollution impacts fetal growth during pregnancy. Exposure to traffic related air pollution was estimated using CALINE4 air dispersion modeling for nitrogen oxides (NOx) and a land use regression (LUR) model for nitrogen mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 35 publications
1
27
1
10
Order By: Relevance
“…Similarly, some studies (Slama et al, 2009;Hansen et al, 2008;Pedersen et al, 2013;Van den Hooven et al, 2012) have reported adverse effects of prenatal exposure to ambient air pollution on head circumference, while others have not (Estarlich et al, 2011;Hansen et al, 2007;Ritz et al, 2014).…”
Section: Introductionmentioning
confidence: 93%
“…Similarly, some studies (Slama et al, 2009;Hansen et al, 2008;Pedersen et al, 2013;Van den Hooven et al, 2012) have reported adverse effects of prenatal exposure to ambient air pollution on head circumference, while others have not (Estarlich et al, 2011;Hansen et al, 2007;Ritz et al, 2014).…”
Section: Introductionmentioning
confidence: 93%
“…Aux États-Unis, une diminution du poids de naissance en rapport avec l'augmentation de la concentration en PM2,5 est observée seulement chez les garçons dont les mères sont obèses, ces dernières représentant 34,5% de la cohorte étu-diée (Lakshmanan et al 2015). De plus, la concentration en NO 2 et autres oxydes d'azote est associée à une diminution du diamètre bipariétal de l'enfant, mais pas nécessairement à un RCIU (Ritz et al 2014 ;Bertin et al 2015). Une corré-lation négative entre la concentration en PM10 et le risque de petit poids de naissance est au contraire observée à Sao Paulo au Brésil : l'augmentation de l'exposition à la pollution serait contrebalancée par le profil socio-économique élevé des familles étudiées (Habermann & Gouveia, 2014).…”
Section: Retard De Croissance Intra-utérinunclassified
“…Este achado não tem paralelo na literatura, pois apenas dois estudos anteriores examinaram a associação entre O 3 e parâmetros de crescimento fetal, e ambos usaram estações fixas de monitoramento do ar, ao invés de monitoramento individual. Esses estudos não encontraram efeito consistente da exposição ao O 3 no crescimento do polo cefálico (28,32) . Contudo, sabe-se que os valores de poluentes medidos de forma individual são mais confiáveis que os medidos por meio de estações fixas (33,35) .…”
Section: Biometria Fetalunclassified
“…Ritz et al (32) (116)(117)(118)(119) . Outra vantagem dos APIs é que, além de medir os poluentes na mesma zona de respiração da gestante, é factível avaliar a exposição à poluição durante as atividades de transporte, trabalho e lazer e em ambientes fechados (35) .…”
Section: Correlação Entre Os Poluentesunclassified
See 1 more Smart Citation